2020
DOI: 10.1246/bcsj.20200054
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transformation of Silica from Natural Resources to Form Tetramethoxysilane

Abstract: A simple and practical method for direct synthesis of tetramethoxysilane (TMOS) from silica (SiO2) and methanol was achieved using a base catalyst and acetal as a dehydrant under carbon dioxide (CO2). The production of TMOS was strongly influenced by the kind of the acetal used, with 2,2-dimethoxypropane identified as the most effective dehydrant. We observed that the acetal used enabled the production of a high yield of dimethyl carbonate (DMC), which promoted the TMOS production. DMC is an intermediate produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Another acetal, 1,1-dimethoxycylohexane, afforded a lower TMOS yield of 36% (entry 4). 19 These results indicated that both CO 2 and the acetals were important for optimizing the TMOS yield. As a dehydrating agent, the acetal was responsible for DMC (dimethyl carbonate) formation and accelerated TMOS production ( Figure 7 ).…”
Section: Synthesis Of Tros From Siomentioning
confidence: 93%
See 2 more Smart Citations
“…Another acetal, 1,1-dimethoxycylohexane, afforded a lower TMOS yield of 36% (entry 4). 19 These results indicated that both CO 2 and the acetals were important for optimizing the TMOS yield. As a dehydrating agent, the acetal was responsible for DMC (dimethyl carbonate) formation and accelerated TMOS production ( Figure 7 ).…”
Section: Synthesis Of Tros From Siomentioning
confidence: 93%
“…The use of excess acetal (25 mmol) significantly increased the TMOS yield to 83% (entry 3). Another acetal, 1,1-dimethoxycylohexane, afforded a lower TMOS yield of 36% (entry 4) . These results indicated that both CO 2 and the acetals were important for optimizing the TMOS yield.…”
Section: Synthesis Of Tros From Sio2mentioning
confidence: 97%
See 1 more Smart Citation
“…At the same time, silicon-based materials play an important role in the field of high technology. The silicon chemical industry is a high consumer of energy (Putro et al 2020) and high generator of pollution (Furgal and Lenora 2019). Thus, it is important to find green and environmentally friendly routes for the synthesis of silicon-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is now possible to depolymerize silica using catalytic base in the presence of alcohols especially diols such as ethylene glycol or hexylene glycol to afford in the later case distillable alkoxysilanes (e. g. spirosiloxanes, SP) in one-pot at low temperature. [12][13][14] Currently obtained by reacting SiCl 4 with alcohols, tetraalkoxysilanes such as tetraethoxysilane (TEOS) and tetramethoxysilane (TMOS) are key precursors to silicabased sol-gel materials. Their direct synthesis at lower cost from biobased silica or replacement with SP would open-up sol-gel applications that remained elusive (e. g. aerogels) due to the high cost of said precursors.…”
Section: Introductionmentioning
confidence: 99%